Soloxolone para-methylanilide effectively suppresses aggressive phenotype of glioblastoma cells including TGF-β1-induced glial-mesenchymal transition in vitro and inhibits growth of U87 glioblastoma xenografts in mice - Odarenko, Kirill V.; Sen’kova, Aleksandra V.; Salomatina, Oksana V.; Markov, Oleg V.; Salakhutdinov, Nariman F.; Zenkova, Marina A.; Markov, Andrey V. (Frontiers in Pharmacology, 2024)
Soloxolone amides are semisynthetic triterpenoids that can cross the blood-brain barrier and inhibit glioblastoma growth both in vitro and in vivo. Here we investigate the impact of these compounds on processes associated with glioblastoma invasiveness and therapy resistance. Screening of soloxolone amides against glioblastoma cells revealed the ability of compound 7 (soloxolone paramethylanilide) to inhibit transforming growth factor-beta 1 (TGF-β1)-induced glial-mesenchymal transition (GMT). Compound 7 inhibited morphological changes, wound healing, transwell migration, and expression of mesenchymal markers (N-cadherin, fibronectin, Slug) in TGF-β1induced U87 and U118 glioblastoma cells, while restoring their adhesiveness. Confocal microscopy and molecular docking showed that 7 reduced SMAD2/3 nuclear translocation probably by direct interaction with the TGF-β type I and type II receptors (TβRI/II). In addition, 7 suppressed stemness of glioblastoma cells as evidenced by inhibition of colony forming ability, spheroid growth, and aldehyde dehydrogenase (ALDH) activity. Furthermore, 7 exhibited a synergistic effect with temozolomide (TMZ) on glioblastoma cell viability. Using N-acetyl-L-cysteine (NAC) and flow cytometry analysis of Annexin V-FITC-, propidium iodide-, and DCFDA-stained cells, 7 was found to synergize the cytotoxicity of TMZ by inducing ROS-dependent apoptosis. Further in vivo studies showed that 7, alone or in combination with TMZ, effectively suppressed the growth of U87 xenograft tumors in mice. Thus, 7 demonstrated promising potential as a component of combination therapy for glioblastoma, reducing its invasiveness and increasing its sensitivity to chemotherapy.